Consumer purchasing behaviour for fresh vegetables in Nanjing, China - Liu, A.; Xu, L.; Zhou, S.; Batt, Peter (International Society of Horticultural Science, 2013)
With increasing income and growing concerns for food safety, consumer purchasing behaviour for fresh vegetables is changing in China. To gain a better understanding of consumer behaviour in Nanjing, 542 face-to-face interviews were conducted. Results show that most fresh vegetables are purchased from traditional wet markets several times per week. In evaluating the quality of the fresh vegetables respondents intended to purchase, the two key selection criteria were colour and freshness. Most respondents were aware of some recent food safety incident that had adversely affected the industry. Respondents were most concerned about the presence of pesticide residues. To reduce the possibilities of contamination, respondents chose to wash or soak the fresh vegetables they intended to eat and to buy from trusted suppliers. Consumers believed that farmers, vegetable processors and government should be responsible for the enhancing and maintaining the safety of the fresh vegetables offered for sale.